Natural Disaster Response, Community Resilience, and Economic Capacity: A Case Study of Coastal Florida. Issue 8 (2nd August 2016) - Kim, Hyun; Marcouiller, David W.
ABSTRACT: The strength and resiliency of regional economic and social structure play an important role in responding to and recovering from natural disasters. In this research, we address the economic resilience of coastal regions to natural disasters using county-level panel data. Results suggest that regions with stronger economies before the disaster experienced lower disaster losses. Thus, strengthening economic conditions before disasters strike can help minimize a region's vulnerability to future damage. Further, existing socioeconomic conditions and social capital attributes improved local resiliency as long as exogenous baseline assumptions were well managed or maintained after a natural disaster. Policy implications of these findings are that increasing the adaptive capacity of counties should result in achieving wider societal goals that support resilient coastal development.